Australian twin and molecular genetic study on attention deficit hyperactivity disorder and its co-morbidity with reading disability - Sheikhi, Abdullah (Curtin University, 2008)
Aim: This study aims to investigate the genetic components of Attention Deficit Hyperactivity Disorder (ADHD), Reading Disability (RD), and their comorbidity. Methods: Three approaches were applied to data from 2610 Australian twin families. This data was obtained by parental completion of the ‘Twin and Sibling Questionnaire'. 1) Latent Class Analysis (LCA) was applied to generate genetically independent classes that defined ADHD subtypes and RD based on related cluster symptoms. 2) Genetic modelling was used to study the particular genetic and environmental effects of each ADHD subtype and of RD, and to examine whether children identified with comorbid ADHD-RD are a genetically distinct group from those who have only ADHD without RD. 3) A family-based genetic association, including haplotype block analysis, was applied to compare the efficacy of DSM-IV diagnostic criteria and LCA in the genotyping analysis, to test the genetic overlap of ADHD candidate genes on RD phenotypes.and vice versa, and to detect some of the risk alleles of ADHD alone, RD alone, and comorbid ADHD-RD. This analysis was performed on a data set that included 190 individuals from the original sample; it tested twenty-one Single Nucleotide Polyrnorphisms (SNPs) from five ADHD candidate genes (DRD4, DATI, SNAP25, COMT, and HTR1B), and four RD candidate genes (MRS2L, KIAA0319, TTRAP, and THEM2) from the 6p22.2 region.Results: The LCA dissected the phenotypes for ADHD and RD into nine genetically informative classes. Univariate and bivariate results indicated the presence of unique genetic components on each ADHD subtype and RD category, and also showed the existence of genetic factors for comorbid ADHD-RD. The association findings, using continuous data represented by scores,of DSM-IV-defined ADHD and RD, showed two significant associations for ADHD and RD, whereas the association findings for the categorical data, represented by LCA, were richer as they showed 15 significant single-locus with ADHD and RD latent classes. Some of these association results were between ADHD candidate SNPs with RD latent classes and ADHD-RD comorbid classes. Some RD candidate SNPs were associated with ADHD latent classes and ADHD-RD comorbid classes. Haplotype block analysis detected a presence of one significant haplotype block containing two haplotype-tagging SNPs (ht-SNPs) of the COMT gene (rs4680 and rs165599), including three risk alleles ('AA', 'GC', and 'AC') that were associated with some phenotypic RD components. Conclusion: This study found that the use of ADHD-RD latent classes is more suitable for performing genetic association studies and haplotype block analysis than is DSM-IV- defined ADHD and RD definitions. Furthermore, there is an overlapping of genetic effect, as ADHD candidate genes contributed to RD phenotypes and vice versa. Thirdly, ADHD-RD comorbidity is caused by both ADHD and RD candidate genes.